'Master in the Art of Holy Living': The Sanctity of William Stevens. (4th January 2016) - Andrews, Robert
Abstract : The following paper explores the sanctity of the late eighteenth-century High Church Anglican layman, William Stevens (1732—1807), as seen through the eyes of his biographer, Sir James Allan Park (1763–1838). A largely unstudied figure, Stevens, a prosperous London hosier who dedicated most of his adult life to philanthropic, theological and ecclesiastical concerns, arguably represents one of the most important figures within pre-Tractarian High Churchmanship. Park was a close friend of Stevens. A judge of the Common Pleas and a founding member of Stevens's 'Club of Nobody's Friends', Park shared Stevens's interest in theology and church-related concerns, even publishing in 1804 a short discourse directed towards young people, on the need for a frequent reception of Holy Communion. In focus here is a facet of Stevens's life that came to be closely associated with his many achievements as a lay divine and activist within the pre-Tractarian Church of England, namely, his personal sanctity; this was marked by a close connection between faith and works, a strict dedication and devotion to the Church of England's services and sacraments, and a rejection of'enthusiasm' in its pejorative sense — all of which he held while maintaining a strong sense of cheerfulness and zeal. A portrait of sanctity that conforms to what is known about pre-Tractarian spirituality, the Memoirs may additionally be viewed as offering a representative understanding of what constituted holiness for this Anglican tradition.